2016
DOI: 10.1590/1414-431x20155020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microRNA-21 on the proliferation of human degenerated nucleus pulposus by targeting programmed cell death 4

Abstract: This study aims to explore the effect of microRNA-21 (miR-21) on the proliferation of human degenerated nucleus pulposus (NP) by targeting programmed cell death 4 (PDCD4) tumor suppressor. NP tissues were collected from 20 intervertebral disc degeneration (IDD) patients, and from 5 patients with traumatic spine fracture. MiR-21 expressions were tested. NP cells from IDD patients were collected and divided into blank control group, negative control group (transfected with miR-21 negative sequences), miR-21 inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…Diminished PDCD4 expression was previously reported in head and neck squamous cell carcinoma [ 80 ], lung cancer [ 81 ], bladder cancer [ 82 ], and colon adenocarcinoma [ 83 ] compared to normal tissues. PDCD4 is involved in cell apoptosis, neoplastic transformation, and tumor progression [ 84 , 85 ]. PDCD4 exerts its function by binding to the eukaryotic translation initiation factor 4A1 and hindering mRNA translation initiation and capping [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diminished PDCD4 expression was previously reported in head and neck squamous cell carcinoma [ 80 ], lung cancer [ 81 ], bladder cancer [ 82 ], and colon adenocarcinoma [ 83 ] compared to normal tissues. PDCD4 is involved in cell apoptosis, neoplastic transformation, and tumor progression [ 84 , 85 ]. PDCD4 exerts its function by binding to the eukaryotic translation initiation factor 4A1 and hindering mRNA translation initiation and capping [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…PDCD4 exerts its function by binding to the eukaryotic translation initiation factor 4A1 and hindering mRNA translation initiation and capping [ 86 ]. PDCD4 could also influence different cellular transcriptional pathways in various tumors [ 85 ]. PDCD4 suppressed carbonic anhydrase II (CAII) in human embryonic kidney [ 87 ], delayed cell cycle transition from G1 to S phase in glioma cancer cell [ 88 ], inhibited colon cancer cell invasion through suppressing MAP4K1 [ 89 ], and phosphorylated the specificity protein transcription factors in colorectal cells [ 90 ], thus promoting essential events important in driving invasion and metastasis [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, transfection of human NP cells with miR-21 mimic dramatically increased Akt activity via targeting PTEN, leading to upregulation of cyclin D1 expression and subsequent cell proliferation [ 95 ]. It is worth noting that overexpression of miR-21 could also stimulate these cell proliferation via silencing of programmed cell death 4 (PDCD4) [ 96 ]. Recently, Li et al identified growth arrest specific gene 1 (GAS1) as a direct and functional target of miR-184 [ 97 ].…”
Section: Roles Of the Pi3k/akt Pathway In The Pathogenesis Of Iddmentioning
confidence: 99%
“…In addition, a number of studies have demonstrated that dysregulated miRNAs participate in various human cancers and act as oncogenes or suppressor genes, depending the function of their targets (16,17). Additionally, several miRNAs were reported to regulate various target genes, pathways and processes essential for the pathogenesis of IDD (18)(19)(20). However, although miRNAs have been investigated extensively in recent years, their roles in IDD development, and as potential markers for microRNA-96 regulates the proliferation of nucleus pulposus cells by targeting ARID2/AKT signaling diagnosis and prognosis, remain unclear.…”
Section: Introductionmentioning
confidence: 99%